Design of profile controller for biochemical reactor - Gharahvaran, Arash Assadzadeh (2010)
The biotechnology industry is growing sharply due to progress in understanding of complex biological systems and high demand for chemical and biologically manufactured products. Bioreactors are used for the production of materials like ethanol, or extraction of enzymes from microorganisms, animal or plant cells. In order to maximize the productivity, the bioreactor needs optimal conditions for process parameters such as pH, temperature, and dissolved oxygen (DO). The goal of achieving high performance controller is the answer to these demands. There are many types of process controllers like the ON/OFF controller, PID controller, and controller based on an artificial intelligence. Neural network and PID controllers have been used together to learning system features, and to reduce the residual error as well as to replace currently PID controllers in the proposed design. This research focuses on designing a profile controller for pH, DO, and temperature that affects production of ethanol. The temperature is controlled by the following a cooling agent, and the pH is controlled by adding the appropriate amount of base or acid, while the dissolved oxygen is controlled by changing the speed of the stirrer. The inputs to the bioreactor are cooling agent (Fag), flow of base (Fb), and stirring speed of the liquid (Nstir). The parameters that need to follow a given profile are temperature, pH, and dissolved oxygen.